(U-Th)/He ages of phosphates from Zagami and ALHA77005 Martian meteorites: Implications to shock temperatures. (1st January 2017) - Min, Kyoungwon; Farah, Annette E.; Lee, Seung Ryeol; Lee, Jong Ik
Abstract: Shock conditions of Martian meteorites provide crucial information about ejection dynamics and original features of the Martian rocks. To better constrain equilibrium shock temperatures ( Tequi-shock ) of Martian meteorites, we investigated (U-Th)/He systematics of moderately-shocked (Zagami) and intensively shocked (ALHA77005) Martian meteorites. Multiple phosphate aggregates from Zagami and ALHA77005 yielded overall (U-Th)/He ages 92.2 ± 4.4 Ma (2 σ ) and 8.4 ± 1.2 Ma, respectively. These ages correspond to fractional losses of 0.49 ± 0.03 (Zagami) and 0.97 ± 0.01 (ALHA77005), assuming that the ejection-related shock event at ∼3 Ma is solely responsible for diffusive helium loss since crystallization. For He diffusion modeling, the diffusion domain radius is estimated based on detailed examination of fracture patterns in phosphates using a scanning electron microscope. For Zagami, the diffusion domain radius is estimated to be ∼2–9 μm, which is generally consistent with calculations from isothermal heating experiments (1–4 μm). For ALHA77005, the diffusion domain radius of ∼4–20 μm is estimated. Using the newly constrained (U-Th)/He data, diffusion domain radii, and other previously estimated parameters, the conductive cooling models yield Tequi-shock estimates of 360–410 °C and 460–560 °C for Zagami and ALHA77005, respectively. According to the sensitivity test, the estimated Tequi-shock values are relatively robust to input parameters. The Tequi-shock estimates for Zagami are more robust than those for ALHA77005, primarily because Zagami yielded intermediate fHe value (0.49) compared to ALHA77005 (0.97). For less intensively shocked Zagami, the He diffusion-based Tequi-shock estimates (this study) are significantly higher than expected from previously reported Tpost-shock values. For intensively shocked ALHA77005, the two independent approaches yielded generally consistent results. Using two other examples of previously studied Martian meteorites (ALHA84001 and Los Angeles), we compared Tequi-shock and Tpost-shock estimates. For intensively shocked meteorites (ALHA77005, Los Angeles), the He diffusion-based approach yield slightly higher or consistent Tequi-shock with estimations from Tpost-shock, and the discrepancy between the two methods increases as the intensity of shock increases. The reason for the discrepancy between the two methods, particularly for less-intensively shocked meteorites (Zagami, ALHA84001), remains to be resolved, but we prefer the He diffusion-based approach because its Tequi-shock estimates are relatively robust to input parameters.